Evidence from two transformed cell lines that the phosphorylations of peptide tyrosine and phosphatidylinositol are catalyzed by different proteins. - MacDonald, M L (1985)
Two transformed rodent cell lines (RS-1 and LSTRA) were studied in vitro to determine if their major protein tyrosine kinases catalyzed the phosphorylation of phosphatidylinositol (PtdIns), phosphatidylinositol 4-phosphate (PtdIns4P), or diacylglycerol. RS-1 cells, transformed by Rous sarcoma virus, contain high levels of pp60src; LSTRA cells, transformed by Moloney murine leukemia virus, contain a tyrosine kinase (pp56) that is the product of an unknown cellular gene. Rates of phosphorylation of peptide tyrosine were elevated more than 20-fold in RS-1 and LSTRA particulate fractions compared to fractions from suitable control cells (N2 and YAC-1), but there was not a proportional increase in rates of phosphorylation of PtdIns, PtdIns4P, or diacylglycerol. Heat (34 degrees C) completely inactivated the LSTRA tyrosine kinase, while it enhanced the phosphorylation of PtdIns and PtdIns4P and had no effect on the phosphorylation of diacylglycerol. PtdIns4P inhibited the phosphorylation of PtdIns but had no effect on tyrosine kinase activity. An antibody, raised against a peptide with a sequence homologous to the autophosphorylation site of pp60src, immunoprecipitated tyrosine kinase activity from RS-1 and LSTRA extracts but had no effect on PtdIns kinase or PtdIns4P kinase activity. These results provide evidence that the phosphorylations of tyrosine and PtdIns are catalyzed by different proteins. An additional observation was that a monoclonal antibody that binds to pp60src and pp56 removed PtdIns kinase as well as tyrosine kinase activity from RS-1 and LSTRA particulate extracts. This antibody also removed PtdIns kinase from N2 and YAC-1 extracts, in which tyrosine kinase activity was low or undetectable. Thus, the anti-pp60src monoclonal antibody may recognize the PtdIns kinase in addition to pp60src and pp56.